PERSPECTIVES FOR INVESTING AND TRADING FOR CRYPTOCURRENCY ETHEREUM - Семеген, Ірина; Слісарчук, Юрій (Socio-economic relations in the digital society, 2019)
In this article, authors review the market of cryptocurrency, and determines it’s place in the global financial system. Virtual currency inherently diff erent from the usual for users electronic money, because the last one is digital display of real money (in modern researches — fiat money), in the process of circulation and exchange between financial market participants within the real economy with offi cial legal status. It has been established that to used widely crypto-currency in the economy of the country, it is appropriate to consider the development of cpyptoindustry at the state level. Attention is focused on analyzing the advantages and disadvantages of cryptocurrency ethereum. A comparative analysis of bitcoin and ethereum cryptocurrency from the point of view of investment and trading perspectives is conducted. It is established that cryptocurrency bitcoin is used in circulation mainly as a means of payment, in comparasion to the ethereum, from the position of functionality. To the main advantages of using ethereum on the cryptocurrency market, the authors attribute such characteristics as it’s universality, flexibility and accessibility. The authors carried out a correlation analysis of the dependence of the ethereum exchange rate on the exchange rate of bitcoin. It was found out that the key factor infl uencing the cost of cryptocurrency ethereum is the state of the cryptocurrency market (it’s volatility) and the bitcoin exchange rate. The authors note that cryptocurrency ethereum has broad prospects for investing, but these investments will be profitable only in the long-term investment period. It has been established that cryptocurrency market used to developed very fast and it is quite possible that it will replace the usual electronic money in a next few years.